In Situ Heat Shock Protein Degradation by Combined PROTAC for Enhanced NIR-II Mild Phototheranostics - Yating Wang; Yixuan Xu; Dejia Chen; Dalong Yin; Lifeng Yan (ACS Nano Medicine, 2026)
Abstract Abstract photothermal therapy (PTT) usually results in the increase of heat shock proteins (HSPs), which leads to side effects and low efficiency. Protein degradation-targeting chimeras (PROTAC) provides a chance to degrade the HSPs, but the smart PROTAC during PTT is still scarce. Here, we designed and constructed a PROTAC-loaded peptide nanoparticle (PJS) for near-infrared II (NIR-II) fluorescence imaging-guided and mild tumor photothermal/photodynamic synergistic therapy. The nanoparticles self-assembled from acid-sensitive amphiphilic polypeptides, encapsulating both the photodynamic/photothermal dual-effect photosensitizer TPBr-Cy and the PROTAC molecules targeting heat shock protein 90 (HSP90) degradation. PJS exhibited good biocompatibility and responsiveness to the acidic tumor microenvironment. Upon accumulation at tumor sites and responsive release, the enhanced fluorescence signal of TPBr-Cy enabled high-resolution NIR-II fluorescence imaging, providing navigation for precision therapy. Under single near-infrared laser irradiation, PJS simultaneously generated reactive oxygen species (ROS) for PDT effects while effectively maintaining local temperatures within the mild photothermal range (∼45 °C), minimizing the thermal damage to surrounding normal tissues. Crucially, the released PROTAC molecules specifically degraded HSP90 protein, effectively disrupting tumor cells’ heat defense mechanisms under mild thermal stress and significantly enhancing sensitivity to mild photothermal therapy. This intelligent responsive peptide nanoplatform, integrating NIR-II imaging, PROTAC-mediated protein degradation, PDT, and mPTT, demonstrated promising synergistic antitumor effects.